The role of mapping in disaster management - Shrestha, Kalyan Gopal (Journal on Geoinformatics, Nepal, 2006)
Every year Nepal suffers from many kinds of disasters such as floods and landslides. In recent years, the increasing numbers of natural disasters in Asia like Tsunami and series of South Asian quakes are a matter of serious concern to us. At this crucial period, we should be conscious about our status of disaster management situation in Nepal. What will happen if a strong earthquake or any other natural disaster strikes Nepal, particularly in the capital city of Kathmandu? Though we cannot avoid disaster, but by implementing the effective prevention schemes, we can reduce damages from severity, if sufficient information for disaster forecasting is given timely. This paper attempts to evaluate the critical role of mapping for all stages of the disaster management cycle: prevention, mitigation, preparedness, response and recovery.